Deciphering the Role of Adrenergic Receptors in Alzheimer’s Disease: Paving the Way for Innovative Therapies - Androulla N. Miliotou; Andria Kotsoni; Lefteris C. Zacharia (Biomolecules)
Neurodegenerative diseases are currently among the most devastating diseases with no effective disease-modifying drugs in the market, with Alzheimer’s disease (AD) being the most prevalent. AD is a complex multifactorial neurodegenerative disorder characterized by progressive and severe cognitive impairment and memory loss. It is the most common cause of progressive memory loss (dementia) in the elderly, and to date, there is no effective treatment to cure or slow disease progression substantially. The role of adrenergic receptors in the pathogenesis of Alzheimer’s disease and other tauopathies is poorly understood or investigated. Recently, some studies indicated a potential benefit of drugs acting on the adrenergic receptors for AD and dementias, although due to the heterogeneity of the drug classes used, the results on the whole remain inconclusive. The scope of this review article is to comprehensively review the literature on the possible role of adrenergic receptors in neurodegenerative diseases, stemming from the use of agonists and antagonists including antihypertensive and asthma drugs acting on the adrenergic receptors, but also from animal models and in vitro models where these receptors have been studied. Ultimately, we hope to obtain a better understanding of the role of these receptors, identify the gaps in knowledge, and explore the possibility of repurposing such drugs for AD, given their long history of use and safety.